(3+2) Annulation of Amidinothioureas with Binucleophile: Synthesis and Antimicrobial Activity of 3‐Phenylamino‐5‐aryl/alkyl‐1, 2, 4‐oxadiazole Derivatives. (12th May 2014) - Yerande, Swapnil G.; Ghaisas, Amruta B.; Newase, Kiran M.; Wang, Wei; Wang, Kan; Dömling, Alexander
<x xml:space="preserve">Abstract</x> Herein, we report an efficient method for preparation of 3‐phenylamino‐5‐aryl/alkyl‐1, 2, 4‐oxadiazole by (3+2) annulation of amidinothioureas with binucleophilic hydroxylamine hydrochloride in the presence of mercury (II) chloride. Desired 3‐phenylamino‐5‐aryl/alkyl‐1, 2, 4‐oxadiazole was prepared in good to moderate yields. On the basis of the literature precedence, the mechanism for the formation of 3‐phenylamino‐5‐aryl/alkyl‐1, 2, 4‐oxadiazole is proposed. The synthesized compounds were tested for their antimicrobial activity and showed promising inhibition of Gram‐positive bacteria (Staphylococcus aureus) and fungi (Candida albicans).